1999
DOI: 10.1080/089583799196790
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Biomarkers of Ozone Exposure in Human Plasma, Nasal Lavage, and Sputum

Abstract: We examined ozone-induced upper and lower airway inflammatory responses and the concentrations of hydroxylated salicylate metabolites using nasal lavage fluid and induced sputum, in order to identify noninvasive and sensitive biomarkers for ozone exposure and effects. A time course for plasma concentration of 2, 3-dihydroxybenzoic acid (2,3-DHBA, a salicylate metabolite and an indicator for hydroxyl radical) in response to 0.12 ppm ozone was also studied. Healthy, young, nonsmoking volunteers were given acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…These studies consistently demonstrated reversible pulmonary function decrements and transient symptoms. Some studies have also noted enhanced bronchial reactivity (Folinsbee and Hazucha 2000;Foster et al 2000) and airway inflammation (Kim et al 2011;Liu et al 1999). Such studies have also investigated different types of exposure regimens; for example, some studies have involved square wave exposures, where ozone concentration is maintained at a constant value throughout the exposure period.…”
Section: Human Clinical Studies Of Ozonementioning
confidence: 99%
“…These studies consistently demonstrated reversible pulmonary function decrements and transient symptoms. Some studies have also noted enhanced bronchial reactivity (Folinsbee and Hazucha 2000;Foster et al 2000) and airway inflammation (Kim et al 2011;Liu et al 1999). Such studies have also investigated different types of exposure regimens; for example, some studies have involved square wave exposures, where ozone concentration is maintained at a constant value throughout the exposure period.…”
Section: Human Clinical Studies Of Ozonementioning
confidence: 99%